EVALUASI KAPASITAS BENDUNG UNTUK PERENCANAAN CHECKDAM SEBAGAI PENGENDALIAN SEDIMENTASI DI BENDUNG LOGUNG - Utomo, Pambudi Nur; Solikin, Mochamad; Pudyastuti, Purwanti Sri; Sunarjono, Sri (Politeknik Negeri Semarang, 2024)
Sedimentation that occurs in the Logung Weir in Kudus Regency can reduce the capacity of irrigation services. The conturmeisure for sediment by build a check dam or normalization. The methods used in this analysis include hydrological analysis using the Hec-HMS application to obtain a 50 year planned flood discharge, erosion rate analysis using the Universal Soil Loss Equation (USLE) method and sediment analysis using the Sediment Delivery Ratio (SDR) method. Furthermore, comparing the efficiency between normalization work and making check dams and their maintenance. Analysis of the amount of sediment in the Logung Dam catchment is 1.18 mm/year with a sedimentation rate of 0.27%, which is 4750.87 m ³/year. The sediment storage capacity at Logung Weir is 1,918.00 m ³, it is necessary to increase the storage capacity of 2,832.61 m ³. For scenario 1, normalization/dredging is carried out 3 times a year, with an operational cost of IDR 707,425,977.00/year. Within a period of 50 years the total cost that must be incurred is Rp. 155,503,120,928.41. Scenario 2 is the construction of a check dam at the upstream of Logung Weir, the location is suggested at Sta. 11+50. The cost required Rp. 4,171,067,132.16 for construction and annual dredging costs of Rp. 235,808,659.01. Within a period of 50 years the total costs to be incurred amounted to 56,005,440,774.97. Comparison of the 2 scenarios shows that a more efficient long-term value is the construction of check dams and their operations.